Riparian buffer zones widths, windthrows and recruitment of dead wood : A study of headwaters in northern Sweden - Nilsson, Gustaf (SLU/Dept. of Forest Ecology and Management, 2021)
Riparian buffer zones, that is vegetated strips that are left surrounding streams, are today the general management practice to protect our running waters during forestry. They are created with the intent of preserving a variety of important ecological functions, including provision of dead wood. In this study, I wanted to investigate how buffer width affects windthrows and recruitment of dead wood in the buffer zones of 29 headwater streams in Västerbotten, Sweden. I registered and measured all dead trees rooted within the buffer zones. I also measured original and current buffer width. The original width was given by the uprooted outer edge trees and the current width was given by the current standing outer edge trees. Further, I gathered landscape properties such as clear-cut size, harvest year, clear-cut slope, stream direction and buffer zone soil wetness to use for statistical analysis. A weak, near significant relationship of decreasing buffer zone loss with increasing buffer zone width was found. Although weak, this result could indicate that narrower buffer zones are more prone to wind damage and managers should create wider buffer zones to minimize windthrows. I found similar amounts of dead wood in the buffers regardless of the buffer width. This implies that the buffer widths used today for headwaters in Sweden today are equally vulnerable to windthrows and that narrower buffers are experiencing the same loss of retained trees as the wider buffers. No other measured parameter was significantly affecting the amount of dead wood in the buffers. Further studies are needed to increase knowledge on how windthrows affect the buffer zones intended ecological functions.